2017
DOI: 10.1080/09513590.2017.1399693
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone co-treatment in IVF/ICSI cycles in poor responders

Abstract: To estimate the efficacy of growth hormone (GH) co-treatment within an antagonist protocol in IVF/ICSI cycles in poor responders. A prospective observational study involving 50 patients underwent a standard antagonist protocol with or without GH co-treatment. GH was administered by a daily subcutaneous injection of 1,33 mg (equivalent to 4 IU) starting from day 1 of ovarian stimulation until the day of 10,000 human chorionic gonadotropin (hCG) triggering . Concentrations of GH, insulin-like growth factor I (IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Nonetheless, the report demonstrated that GH patients reached oocyte retrieval faster than non-GH patients, as also shown in other studies [9], which may indicate that GH has an effect on folliculogenesis; however, this possibility was not supported by differences in embryo quality [8]. Nonetheless, the links between GH and folliculogenesis, oocyte quality and responsiveness to gonadotrophins is still unclear [2,9,11]. The authors also indicated that while there was no difference in the number of oocytes retrieved or transferred, the low recruitment numbers may mask any perceived improvements [8].…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…Nonetheless, the report demonstrated that GH patients reached oocyte retrieval faster than non-GH patients, as also shown in other studies [9], which may indicate that GH has an effect on folliculogenesis; however, this possibility was not supported by differences in embryo quality [8]. Nonetheless, the links between GH and folliculogenesis, oocyte quality and responsiveness to gonadotrophins is still unclear [2,9,11]. The authors also indicated that while there was no difference in the number of oocytes retrieved or transferred, the low recruitment numbers may mask any perceived improvements [8].…”
Section: Introductionsupporting
confidence: 84%
“…In accordance with this previous work on fresh transfers [12,13], the current findings indicated that the use of GH as an adjuvant cotreatment during IVF stimulation had a positive outcome on fresh ET and in addition, in subsequent FET cycles. As GH was not administered during the FET cycles, this suggested that the potential beneficial effects of GH may extend to embryo quality as presented previously [5,9,16], rather than involving an effect on endometrium receptivity [15,17]. However, in our previous studies on embryos generated under GH action, we failed to demonstrate that the adjuvant altered embryo quality to a measurable extent, as the proportion of highquality embryos on morphological assessment was the same with or without GH [12,13].…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations